Failure of Exclusive Breastfeeding and Inadequate Frequency of Complementary Feeding as Predictors of Stunting - Giyawati Yulilania Okinarum (Media Keperawatan Indonesia, 2021)
In Indonesia, stunting is still a chronic nutritional problem. Many factors influence the prevalence of stunting, including a history of exclusive breastfeeding and the frequency of complementary feeding. The purpose of this study is to determine how much of an impact the exclusive breastfeeding and frequency of complementary feeding has on stunting. This observational analytic study was conducted from July to September 2019 using a case control approach. Samples of 80 children aged 12-24 months, with details of toddlers case group (stunting) and control (normal) 40 each, with inclusion criteria of birth weight and normal gestational age in Yogyakarta. Stratified random sampling was used for sampling. Filling out questionnaires and conducting interviews were used to collect data on characteristics, breastfeeding, and early complementary feeding. Nutritional status is calculated using height/age. Multivariate analysis by multiple logistical regression test revealed statistically significant correlations between stunting and non-exclusive breastfeeding (adjusted OR for exclusive breastfeeding 5,17; 95% CI 1,87 to 14,31) as well as inadequate frequency of complementary feeding (adjusted OR 3,85; 95% CI 1,32 to 11,18). This value implies that exclusive breastfeeding and adequate frequency of complementary feeding are the most dominant protecting factors against stunting. In children aged 12-24 months, the histories of non-exclusive breastfeeding and inadequate frequency of complementary feeding are significantly correlated with stunting.